Measuring the FDI attractiveness in the EAP countries from an institutional perspective - Sorcaru, Sergiu Lucian; Nuta, Florian Marcel; Topliceanu, Stefan Catalin; Ambrozie, Alisa Mihaela (Journal of Business Economics and Management, 2023)
Countries in the European Union’s neighborhood, such as those in the Eastern Partnership (EaP), have a particular interest in attracting foreign direct investment (FDI) because investment inflows can guarantee them a number of advantages needed for accession. This paper proposes a comparative analysis of the investment attractiveness of the EaP countries in the period 2005–2019 considering the institutional theory of FDI inflows. The research methodology considers a quantitative approach that uses the composite index as a tool. The results show that half of the EaP countries have a high level of investment attractiveness, while the institutional quality has an important influence on attracting FDI. First published online 09 January 2024